Seasonality of crime in Croatia : a relationship with tourism - Mataković, Hrvoje (Array, 2020)
Peace, safety, and security are the primary conditions for successful tourism development and security threats such as terrorism, crime or potential war conflicts can strongly affect tourism. Of these threats, crime is the most widespread. Certain types of crime are seasonal and some criminal offences are more often committed at a particular time of the year, week or day. The aim of this paper is to determine whether there is a connection between the seasonality of crime and tourism in Croatia. In order to achieve this aim, the correlation analysis was applied on monthly data from 2007 to 2018, using Pearson product-moment correlation coefficient to measure the strength of the relationship between crime and tourism. The analysis covered reported criminal offences that may be related to tourism. The conducted analysis found a statistically significant correlation between the tourist arrivals and stays and almost all types of reported criminal offences, and this correlation was stronger for property crimes and weaker for violent crimes. The obtained results can help law enforcement agencies to allocate police officers in specific periods of time and thus to provide adequate resources to respond to crime, such as additional police officers during the summer or other seasons.